Gambaran Pemeriksaan Tes Toleransi Glukosa Oral Pada Ibu Hamil Trimester II Dan III - Margareta, Rehza Endza (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Gestational diabetes mellitus (GDM) is a condition of glucose intolerance that occurs during pregnancy which is detected by examining blood glucose levels. This study aims to measure fasting blood glucose levels in pregnant women in the second and third trimesters at RSIA Sayyidah, East Jakarta based on certain characteristics.. Using the GOD-PAP method and this type of research is descriptive quantitative and uses a probability sampling technique with a simple random sampling method. The sample in this study amounted to 37 women. The results of the study obtained 15 (53.57%) pregnant women aged 22-29 years and 13 (46.43%) aged 30-38 years with a total of 28 women in the non-GDM risk category and the results of the study showed that they were in the GDM risk category at the age of 21-29 years as many as 5 (55.56%) and at the age of 32-35 years as many as 4 (44.44%) with a total of 9 women. The conclusion of this study was that fasting blood sugar levels in pregnant women in the second and third trimesters at RSIA Sayyidah, East Jakarta ranged from 70-238 mg/dL.